1955
DOI: 10.1017/s0007485300030753
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence and Fate of DDT on Foliage. I.—The Influence of Plant Wax on the Toxicity and Persistence of Deposits of DDT Crystals

Abstract: The persistence and toxicity of DDT crystals on thin layers of plant wax were studied. Deposits of crystalline DDT at rates of 2 to 8 microgm. per sq. cm. were applied to glass plates, plain or coated with a 0·5 μ layer of wax obtained from leaves of sisal or cabbage. The plates were stored for various periods at 18°C. and at 43°C. (representing temperature and tropical leaf-temperatures). DDT remaining after storage was estimated biologically by means of its contact action on adult Tribolium castaneum (Hbst.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1960
1960
1971
1971

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…As shown in Figs. 18 and 19 (FROHBERGER 1949, WARD and BURT 1956, BURT and WARD 1956) persistence on dead material such as glass and paper is much higher than on leaves and fruits. Furthermore, it can be demonstrated that the living state is decisive: living leaves of the same species show much less persistence (measured as increase of the LD50 of flies) than do killed leaves.…”
Section: P)mentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figs. 18 and 19 (FROHBERGER 1949, WARD and BURT 1956, BURT and WARD 1956) persistence on dead material such as glass and paper is much higher than on leaves and fruits. Furthermore, it can be demonstrated that the living state is decisive: living leaves of the same species show much less persistence (measured as increase of the LD50 of flies) than do killed leaves.…”
Section: P)mentioning
confidence: 99%
“…Loss of DDT deposits from glass plates and growing leaves (above) as quantity of DDT residue per em.' of leaf surface, and (below) as persistence measured by insecticidal activity (adapted from WARD and BURT 1956) time (PIELOU and WILLIAMS 1962 a and c). The effect of surface-active agents (surfactants) such as wetters, spreaders, and stickers on the deposits of pesticides on leaves is not always readily predictable.…”
Section: C) Persistencementioning
confidence: 99%
See 2 more Smart Citations
“…For the second experiment, x 2 = 20-0 (20 degrees of freedom); this is not significantly heterogeneous. Burt & Ward (1955) showed that deposits from DDT suspension increase in toxicity to Tribolium castaneum (Hbst.) when stored; it appears that during the first 24 hours there is also an increase in the replicability of the contact effect of the deposit.…”
Section: Replication Of Kill Between Batchesmentioning
confidence: 99%